2018
DOI: 10.1111/1759-7714.12773
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tumor related signaling pathways with known compounds to determine potential agents for lung adenocarcinoma

Abstract: BackgroundThis study compared tumor‐related signaling pathways with known compounds to determine potential agents for lung adenocarcinoma (LUAD) treatment.MethodsKyoto Encyclopedia of Genes and Genomes signaling pathway analyses were performed based on LUAD differentially expressed genes from The Cancer Genome Atlas (TCGA) project and genotype‐tissue expression controls. These results were compared to various known compounds using the Connectivity Mapping dataset. The clinical significance of the hub genes ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…It is known that apoptosis is highly regulated and plays an important role in immune response and tumorigenesis ( 70 , 71 ). The p53 signaling pathway is recognized as a potential risk factor in lung adenocarcinoma tumorigenesis and survival ( 72 ). The observed up-regulation in the p53 signaling pathways suggests potential pathogenic functions of these salivary microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that apoptosis is highly regulated and plays an important role in immune response and tumorigenesis ( 70 , 71 ). The p53 signaling pathway is recognized as a potential risk factor in lung adenocarcinoma tumorigenesis and survival ( 72 ). The observed up-regulation in the p53 signaling pathways suggests potential pathogenic functions of these salivary microbiota.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, up-regulation of central genes (CCNB1, CCNB2, CDK1, CDKN2A, and CHEK1) in the p53 signaling pathway confirmed the p53 signaling pathway as a risk factor for tumorigenesis and survival in LUAD. 36 In addition, the abnormality of the cell cycle pathway accelerates the occurrence of LUAD. Some scholars have found that the p53 gene has an important regulatory role in the cell cycle, apoptosis, and genomic stability.…”
Section: Discussionmentioning
confidence: 99%
“…Following the path set by the CMap 1.0 framework, many drug repositioning studies utilized the resource in a similar way. CMap 1.0 was directly used to reposition drugs for obesity (10), ovarian cancer (11), breast cancer (12), influenza (13), cigarette smoke-induced inflammation (14), gastric cancer (15), inflammatory bowel disease (16), osteogenic differentiation (17), lung adenocarcinoma (18,19), skeletal muscle atrophy (20), and renal cell carcinoma (21); to find compounds with estrogenic activity (22); to induce bone anabolism (17,23); to target cancer stemness (24); and to find radiosensitizing agents for treating lung cancer (25). In most of these studies, the identified drugs and small molecules were experimentally validated in vitro, and in some cases in animal models.…”
Section: Historical Perspective and Initial Signature Collectionsmentioning
confidence: 99%